The Ottoman “Interregnum” in 1402–1413: The International Aspect - Nikolai Gennadjevich Pashkin (Античная древность и средние века, 2018)
After the Battle of Ankara (1402) Ottoman state went through the long crisis of interregnum. Suleyman, Musa and Mehmed, sons of the Sultan Bayezid I (1389–1402), started the struggle for the throne. It was powerfully influenced by the conflict between European states – Venice and Hungary. Their interests clashed in the Balkans. The Treaty of Gallipoli (1403) originated the process. It balanced the interests of Venice, Genoa, the Byzantine Empire and the Turkish ruler of Rumelia Suleyman (1402–1411). But Hungary did not take part in the treaty, and afterwards Hungarian King Sigismund Luxemburg (1387–1437) attempted to upset the balance of power, founded on the treaty. For this purpose Sigismund entered into the alliance with Serbia and then offered the alliance to the Byzantine Emperor Manuel II Palaeologos (1391–1425). The victory of supporters of Hungary in Bosnia was of great importance. Activities of Sigismund provoked retaliatory measures of Venice. In 1409 the Republic claimed rights to Dalmatia. In 1411 diplomatic feud led to the war. Just that very period was the critical phase of the Turkish «interregnum». Musa, who had opposed Suleyman, defeated him and entered into the alliance with Serbia and Walachia. He attacked the Byzantium. As a result, Sigismund lost potential allies. On the contrary Venice gained an advantage form the treaty with the new Turkish ruler. However the subsequent victory of Mehmed partly restored the parity between Hungary and Venice. Mehmed exploited the alliance with the Byzantium. During the Turkish discord the Byzantine Empire had not been interfering in the conflict between Hungary and Venice and only after the victory of Mehmed offered itself as a honest broker. Venice rejected the offer, but the sense of the Byzantine policy is evident. The Byzantine Empire attempted to renew the treaty of 1403 with enlarged membership and to strengthen the alliance with Turks through the international balance of power, the only way to get some pledging of security for the Empire.